The development of an “Engagement in Physical Education” scale - Stringfellow, Andy; Wang, Chih-hsuan; Farias, Claudio F. G.; Hastie, Peter A. (Frontiers in Sports and Active Living, 2024)
Purpose. The purpose of this paper is to present a scale that assesses students' perceptions of their engagement in physical education. The scale assesses all four dimensions of engagement (agentic, cognitive, behavioral, and emotional) in order to be consistent with the contemporary notion of engagement used in current educational research. Method. A total of 231 eighth and ninth-grade students (108 boys, Mage = 14.55) completed a 21-item scale, with items taken from previously validated scales, but with an added string relating to physical education lessons. Following model respecification by the examination of standardized residual covariances to remove items, the factor loading for each of the items on the scale was examined. Results. The results from a confirmatory factor analysis showed that there was psychometric support for an 18-item survey in which each of the four a priori latent variables was kept in the validation of the four-factor hypothesized model. (χ 2 = 226.01, df = 125, χ 2 /df = 1.808, GFI = .903, RMSEA [90% CI] = .061 [.048 -.073]). Conclusion. Given the research on engagement within physical education has been beleaguered by the lack of a robust operational definition, this scale allows for the comprehensive measurement of the different components of engagement.